2017
DOI: 10.4314/sajas.v47i2.16
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quercetin on fertility of frozen-thawed ram epididymal spermatozoa

Abstract: The aim of the present study was to evaluate the effects of quercetin as an antioxidant supplement on frozen-thawed ram epididymal sperm quality. Quercetin is a type of flavonoid antioxidant that is found in plants, with the ability to scavenge free radicals. Twenty testicles from mature rams were collected from a nearby slaughterhouse immediately after slaughter. Epididymal spermatozoa were recovered from the caudal of epididymides by injecting Bracket and Oliphant's (BO) medium retrogradely through the ductu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
4
15
0
2
Order By: Relevance
“…Our CASA analysis revealed that a concentration range of 5–10 μM QUE and 10–25 μM NAR ensured the best sperm motility preservation over a 3-day period of storage, which is the maximum time recommended for the BTS medium [ 3 ]. In the case of QUE, our observations are in agreement with previous reports on goat [ 15 ], human [ 29 ], and ram spermatozoa [ 16 ], suggesting that exposure of male gametes to particularly lower QUE concentrations may lead to a higher sperm motion behavior. Furthermore, pivotal experiments on cryopreserved boar spermatozoa [ 21 ] suggest that low QUE concentrations administered to the freezing and thawing medium improve sperm motility and subsequent fertilization potential.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our CASA analysis revealed that a concentration range of 5–10 μM QUE and 10–25 μM NAR ensured the best sperm motility preservation over a 3-day period of storage, which is the maximum time recommended for the BTS medium [ 3 ]. In the case of QUE, our observations are in agreement with previous reports on goat [ 15 ], human [ 29 ], and ram spermatozoa [ 16 ], suggesting that exposure of male gametes to particularly lower QUE concentrations may lead to a higher sperm motion behavior. Furthermore, pivotal experiments on cryopreserved boar spermatozoa [ 21 ] suggest that low QUE concentrations administered to the freezing and thawing medium improve sperm motility and subsequent fertilization potential.…”
Section: Discussionsupporting
confidence: 93%
“…Preliminary reports suggest that both flavonoids have the ability to protect the sperm plasma membrane and acrosome structures, mitochondrial function, and DNA stability in rabbit [ 13 ] and bovine [ 14 ] spermatozoa subjected to induced oxidative stress. Their potential to provide protection to the structure and function of cryopreserved goat [ 15 ], ram [ 16 ], bull [ 17 ], rooster [ 18 ] or stallion spermatozoa [ 19 ] subjected to cryopreservation has been indicated as well. Nevertheless, both biomolecules have received relatively little attention with respect to porcine semen.…”
Section: Introductionmentioning
confidence: 99%
“…(3). Similar positive effects of quercetin were reported on the sperm viability in rams (47) and boars (24). On the opposite, high concentrations of quercetin (40 and 80 µM) were unfavorable to sperm viability and membranes integrities.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, they have potential to protect spermatozoa in cryopreservation and post-thaw processes (Silva et al, 2012;Ardeshirnia et al, 2017).…”
Section: Application Of Antioxidants To Cell Cultures Is An Effectivementioning
confidence: 99%